Kate Waller Barrett papers - Barrett, Kate Waller, 1858-1925.
Correspondence, speeches, articles, certificates of appointments to civic organizations, master's thesis, and scrapbooks of newspaper clippings relating to Dr. Barrett's work on behalf of women's rights. Her associations with the Daughters of the American Revolution, National American Legion Women's Auxiliary, National Council of Women, National Florence Crittenton Mission, and Needlework Guild of America are reflected in the papers, as well as her efforts to secure national legislation to protect women's rights, including the Mann Act.
Physician and sociologist.
Collection material in English.
Keywords: Daughters of the American Revolution; American Legion. -- Women's Auxiliary; National Council of Women of the United States; National Florence Crittenton Mission; Needlework Guild of America; Women's rights; Women -- Societies and clubs; Physicians; Sociologists